2017
DOI: 10.1021/acs.langmuir.7b00083
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Chemistry in Integrated Porous Space Formed by Molecular Self-Assembly at Liquid–Solid Interfaces

Abstract: Host-guest chemistry in two-dimensional (2D) space, that is, physisorbed monolayers of a single atom or a single molecular thickness on surfaces, has become a subject of intense current interest because of perspectives for various applications in molecular-scale electronics, selective sensors, and tailored catalysis. Scanning tunneling microscopy has been used as a powerful tool for the visualization of molecules in real space on a conducting substrate surface. For more than a decade, we have been investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 122 publications
0
75
0
Order By: Relevance
“…Recent reviews have described a range of demonstrated strengths of solution/solid STM as an experimental probe, including investigations of molecular reactivity 31 and patterning, 32 elucidation of kinetic and thermodynamic processes, 24 and unravelling the details of programmed host/guest assembly in porous molecular networks. 33 Here, we focus on an emerging application of solution/solid STM: its utility as an enabling technology for practical applications of solution-processed self-assembled molecular structures.…”
Section: Jennifer M Macleodmentioning
confidence: 99%
“…Recent reviews have described a range of demonstrated strengths of solution/solid STM as an experimental probe, including investigations of molecular reactivity 31 and patterning, 32 elucidation of kinetic and thermodynamic processes, 24 and unravelling the details of programmed host/guest assembly in porous molecular networks. 33 Here, we focus on an emerging application of solution/solid STM: its utility as an enabling technology for practical applications of solution-processed self-assembled molecular structures.…”
Section: Jennifer M Macleodmentioning
confidence: 99%
“…Two methodologies are available for fabrication of nanoporous surfaces depending on the types of building blocks: intrinsic and extrinsic. [28,29]. Nanoporous monolayers developed with intrinsic building blocks are founded on macrocyclic molecular structures that are pre-designed with a hollow centre and synthesised beforehand and with specific physical and chemical characteristics.…”
Section: Nanoporous Networkmentioning
confidence: 99%
“…The most used extrinsic building blocks are as trimesic acid (TMA) [30,31], dehydrobenzo [12]annulene (DBA) [32][33][34][35][36] and decycanooligophenylenes [37,38]. They form hexagonal nanopores in which pore size may be modulated by changing the chemical composition of each building block [28][29][30]34]. These are the most attractive systems, since it is possible to modify the pore properties using specific building blocks to obtain a desired purpose.…”
Section: Nanoporous Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional supramolecular self-assembly has received a great deal of attention owing to its potential applications in nano-patterning and host-guest structures on surfaces at the molecular level over recent years. [1][2][3][4][5][6] The hydrogen bonding between carboxylic acid groups is the most extensively studied assembly motif for construction of supramolecular assemblies. [7][8][9] Compared with other supramolecular interaction, hydrogen bonding exhibits both high selectivity and directionality, and is suitable to create novel nano-patterning structures with high predictivity.…”
Section: Introductionmentioning
confidence: 99%